Hydrophobic and electrostatic interactions between cell penetrating peptides and plasmid DNA are important for stable non-covalent complexation and intracellular delivery - Upadhya, Archana; Sangave, Preeti C. (Journal of peptide science, 2016)
Cell penetrating peptides are useful tools for intracellular delivery of nucleic acids. Delivery of plasmid DNA, a large nucleic acid, poses a challenge for peptide mediated transport. The paper investigates and compares efficacy of five novel peptide designs for complexation of plasmid DNA and subsequent delivery into cells. The peptides were designed to contain reported DNA condensing agents and basic cell penetrating sequences, octa‐arginine (R8) and CHK6HC coupled to cell penetration accelerating peptides such as Bax inhibitory mutant peptide (KLPVM) and a peptide derived from the Kaposi fibroblast growth factor (kFGF) membrane translocating sequence. A tryptophan rich peptide, an analogue of Pep‐3, flanked with CH3 on either ends was also a part of the study. The peptides were analysed for plasmid DNA complexation, protection of peptide–plasmid DNA complexes against DNase I, serum components and competitive ligands by simple agarose gel electrophoresis techniques. Hemolysis of rat red blood corpuscles (RBCs) in the presence of the peptides was used as a measure of peptide cytotoxicity. Plasmid DNA delivery through the designed peptides was evaluated in two cell lines, human cervical cancer cell line (HeLa) and (NIH/3 T3) mouse embryonic fibroblasts via expression of the secreted alkaline phosphatase (SEAP) reporter gene. The importance of hydrophobic sequences in addition to cationic sequences in peptides for non‐covalent plasmid DNA complexation and delivery has been illustrated. An alternative to the employment of fatty acid moieties for enhanced gene transfer has been proposed. Comparison of peptides for plasmid DNA complexation and delivery of peptide–plasmid DNA complexes to cells estimated by expression of a reporter gene, SEAP. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Hydrophobic and electrostatic interactions between cell penetrating peptides and plasmid DNA are important for stable non‐covalent complexation and intracellular delivery. Comparison of peptides for plasmid DNA complexation and delivery of peptide–plasmid DNA complexes to cells estimated by expression of a reporter gene, SEAP.